A Device for Measuring Conductivity of Dispersions - Maldonado-Saavedra, M (Elsevier B.V., 2014)
A device to measure pulp electrical conductivity in an industrial environment has been developed. It is based on a variable oscillator circuit whose output period of oscillation is proportional to the sample conductivity. This circuit requires a single point for its calibration, which facilitates its use in an industrial environment. A Nexys2 FPGA (Field Programmable Gate Array) is used to measure the oscillation period, display the data on a LCD screen, communicate the information to a computer by RS-232 and manage the switching of sample probes for multiple measurements. Results have confirmed a linear relationship between frequency and resistance over a wide operational range, between 0.1 mS/cm and 10 mS/cm. Its application in an industrial flotation process in order to estimate froth depth and gas hold-up without prior calibration under certain conditions is also explained and validated. © 2014 Elsevier Ltd. All rights reserved.